THE DETERMINANT OF WHISTLEBLOWING INTENSION OF VILLAGE OFFICIALAS A PREVENTION OF FRAUD IN THE DISTRICT OF WONOSARI - Nur Lazimatul Hilma Sholehah; Parmin Ishak (Jurnal Ekonomi dan Manajemen, 2020)
This research aims to: (1) determine how much theeffect of the ethical climate has on whistleblowing intentions; (2) find out how much the effect of the level of seriousness hason whistleblowing intentions; (3) determine the great effect of locus of control on whistleblowing intentions. This type of research is quantitative research. The object of this study is the village officials in Wonosari District. The sampling technique used in this study was the saturated sampling method. Data collection was carried out by applying a survey method using a questionnaire distributed directly to all village officials in Wonosari District.The result of this study showed that (1) the ethical climate has a positive and significant impact on whistleblowing intentions, (2) the level of seriousness is positively and significantly related to whistleblowing intentions, and (3) locus of control gave positive and significant control of whistleblowing intentions. With a mandatory output of accredited national journal